Interaction Effect between Sports Participation and Elite Sports Development - Saeed Khanmoradi; Shirin Zardoshtian; Shahram Fatahi; Geoff Dickson (Universitas Majalengka, 2022)
Elite athlete success in international events and sports development promotes sports participation and this is main concern for many researchers to develop the elite sport. If the economic conditions are not desirable, it is not possible to develop elite sport and promote sports participation to achieve this goal. Economic crises have made the managers employ a deep insight into the effect of the economic conditions of the country on the sport. Therefore, the purpose of this study is to investigate the interaction effect of sports participation and elite sports development with an emphasis on macroeconomic variables using an econometric model with a simultaneous equation approach based on the 2SLS method in Iran. The results showed that inflation and unemployment rates have significant and negative effects on sports participation. Rural household income has a significant and positive effect on sports participation but urban household income has a significant and negative effect on sports participation. Standard of living has a significant and positive effect on sports participation. The effects of sports media, sports budget, and Non-athlete participants on elite sports development are significant and positive. Finally, the interaction effect of sports participation and elite sports development is positive and significant.